Correlation Between Liver Fibrosis Scores (FIB-4, APRI) and Oxidative Stress Biomarkers in Chronic Hepatitis B and C Patients - Muhammad Imran Khan, Adnan ur Rehman, Muhammad Babar, Imran Ali Shaikh, Muhammad Adil Ramzan, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic hepatitis B and C are leading causes of progressive liver fibrosis, largely mediated by persistent inflammation and oxidative stress. Non-invasive indices such as Fibrosis-4 (FIB-4) and Aspartate Aminotransferase to Platelet Ratio Index (APRI) are commonly used for fibrosis assessment; however, their relationship with oxidative stress biomarkers remains underexplored. Methods: This cross-sectional study was conducted on 100 patients with chronic hepatitis B and C at tertiary care hospitals in Peshawar, Pakistan, from February 2022 to February 2023. Liver fibrosis was assessed using FIB-4 and APRI scores. Serum oxidative stress biomarkers, including malondialdehyde (MDA), superoxide dismutase (SOD), and reduced glutathione (GSH), were measured using ELISA. Statistical analysis was performed using Pearson correlation and multivariate regression. Results: The mean FIB-4 and APRI scores were 1.92 ± 0.85 and 1.08 ± 0.52, respectively. MDA levels showed a strong positive correlation with FIB-4 (r = 0.66, p < 0.001) and APRI (r = 0.61, p < 0.001). In contrast, SOD and GSH demonstrated significant negative correlations with both fibrosis indices (p < 0.01). Patients with advanced fibrosis exhibited significantly higher MDA levels and reduced antioxidant levels compared to those with mild fibrosis. Multivariate analysis identified MDA as an independent predictor of fibrosis severity, while SOD and GSH were negative predictors. Conclusion: Oxidative stress is significantly associated with liver fibrosis severity in chronic hepatitis B and C patients. Integration of oxidative stress biomarkers with non-invasive fibrosis scores may enhance the accuracy of liver disease assessment and monitoring. Keywords: Chronic hepatitis B, Chronic hepatitis C, Liver fibrosis, FIB-4, APRI, Oxidative stress, Malondialdehyde, Superoxide dismutase, Glutathione